2D-CuPd nanozyme overcome tamoxifen resistance in breast cancer by regulating the PI3K/AKT/mTOR pathway. (March 2023) - Jiang, Wenwei; Zhong, Suqin; Chen, Ziying; Qian, Jieying; Huang, Xiaowan; Zhang, Hao; Wen, Longping; Zhang, Yunjiao; Yao, Guangyu
Abstract: Tamoxifen is the most commonly used treatment for estrogen-receptor (ER) positive breast cancer patients, but its efficacy is severely hampered by resistance. PI3K/AKT/mTOR pathway inhibition was proven to augment the benefit of endocrine therapy and exhibited potential for reversing tamoxifen-induced resistance. However, the vast majority of PI3K inhibitors currently approved for clinical use are unsatisfactory in terms of safety and efficacy. We developed two-dimensional CuPd (2D-CuPd) nanosheets with oxidase and peroxidase nanozyme activities to offer a novel solution to inhibit the activity of the PI3K/AKT/mTOR pathway. 2D-CuPd exhibit superior dual nanozyme activities converting hydrogen peroxide accumulated in drug-resistant cells into more lethal hydroxyl radicals while compensating for the insufficient superoxide anion produced by tamoxifen. The potential clinical utility was further demonstrated in an orthotopically implanted tamoxifen-resistant PDX breast cancer model. Our results reveal a novel nanozyme ROS-mediated protein mechanism for the regulation of the PI3K subunit, illustrate the cellular pathways through which increased p85β protein expression contributes to tamoxifen resistance, and reveal p85β protein as a potential therapeutic target for overcoming tamoxifen resistance. 2D-CuPd is the first reported nanomaterial capable of degrading PI3K subunits, and its high performance combined with further materials engineering may lead to the development of nanozyme-based tumor catalytic therapy.